Cross-functional interconnectedness as an enabler of customer value. Issue 4 (7th June 2019) - Seno, João Paulo; Pimenta, Marcio Lopes; Hilletofth, Per; Eriksson, David
Abstract : Purpose: The purpose of this study is to analyze the processes of interconnectedness in cross-functional relationships involved in customer value enabling. Design/methodology/approach: In total, 20 in-depth interviews were conducted in three Brazilian companies from different industries. The critical incident technique was used for data collection and analysis. Content analysis was used to characterize the critical incidents within functional area networks. Findings: Six main critical incidents were identified within the studied relationships: process, urgency, lack of trust, capacity and demand imbalance, motivation and challenge. The results show situations in which the collaborative behavior of the actors generates customer value facilitation. Research limitations/implications: The firms studied are small and medium, located in an emerging economy and are resource-constrained. Further research could be performed in organizations in other countries with different sizes and resources. Future studies could also include customers within the analyzed functional networks to evaluate value-in-use behavior. Practical implications: Process, as a critical incident, may be composed of several elements that could affect the processes of value creation. Moreover, the adjustment between production capacity and demand should focus on avoiding propagation of functional problems through the processes. This focus may facilitate spontaneous community behavior and customer knowledge renewal. Originality/value: This paper generates new qualitative bases to characterize the interconnectedness within functional networks within the perspective of relationship marketing. The study of the internal functions and processes revealed several particularities that are not evidenced in the extant literature, which is concentrated in relationships among companies. The quality of the relationship among the members of a functional network may affect the effectiveness of the promises of customer value, more specifically in value enabling.